Remembering Denny - Trillin, Calvin (Farrar Straus Giroux, 1993)
But life worked out differently for Denny Hansen. After some early jobs in government and journalism, he concentrated on foreign affairs, eventually becoming a professor at the Johns Hopkins School of Advanced International Studies in Washington. He gradually lost touch with his family and his old friends. As time passed, his sunny disposition was overtaken by "all sorts of serious problems - physical, psychological, and maybe even spiritual." Trillin's memoir is an attempt to chart the mysterious course of a life that had seemed full of limitless promise. It is also an investigation of the American fifties - of the assumptions that Trillin and his generation inherited and how those assumptions fared during the transformation of American society over the next forty years. Remembering Denny is a meditation on our country's evolving sense of itself